Alterted SLIT2/ROBO1 signalling is linked to impaired placentation of missed and threatened miscarriage in early pregnancy. Issue 4 (11th July 2017) - Li, Ping; Shi, Yuxun; Shuai, Hanlin; Cai, Yanzhen; Lu, Wenhui; Wang, Guang; Gao, Lufen; Wang, Lijing; Fan, Xiujun; Yang, Xuesong
Abstract : Aims: Two‐thirds of early pregnancy failures present with reduced trophoblast invasion, and SLIT2/ROBO1 signalling is considered to play an important role in trophoblast function during pregnancy. We investigated SLIT2/ROBO1 signalling associated with missed and threatened miscarriage during early gestation. Methods and results: Human placenta samples were collected from women with missed miscarriage ( n = 25), threatened miscarriage ( n = 22) and termination of pregnancy controls ( n = 32). Corresponding decreases in beta human chorionic gonadotrophin (β‐hCG) levels and shallow trophoblast invasion were observed in patients with missed and threatened miscarriage, immunohistological staining revealed abnormal Slit2 and Robo1, as well as E‐cadherin and activating protein‐2 alpha (AP‐2α) expression in villi and extravillous trophoblasts, and the expression of these proteins were confirmed in villi and decidua of miscarriage material by Western blotting. Using HTR8/SVneo cells, blocking SLIT2/ROBO1 signalling promoted cell migration, proliferation and suppressed differentiation. Moreover, blocking SLIT2/ROBO1 signalling in HTR8/SVneo cells altered trophoblast differentiation‐related and angiogenesis‐related gene mRNA expression, which also occurred in the tissues of missed and threatened miscarriage. Conclusions: SLIT2/ROBO1 signalling may regulate trophoblast differentiation and invasion causing restricting β‐hCG production, shallow trophoblast invasion and inhibiting placental angiogenesis in missed and threatened miscarriage during the first trimester.